Role of micronized progesterone in prevention of preterm labour in women with previous history of one or more preterm births: a research study at a tertiary care hospital - Ahuja, Rashmi; Sood, Anupa; Pal, Anita; Mittal, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: According to the WHO, 3 million newborns die each year due to complications related to pregnancy and childbirth and 99% of these deaths occur in the developing countries. Preterm birth is a leading cause of neonatal and infant mortality as well as short and long term disability. The mechanism responsible for preterm labour are not exactly known, may be multifactorial and preventable with timely and appropriate treatment. Methods: This was a prospective double blinded randomized placebo controlled study conducted in the department of Obstetrics and Gynaecology, Kamla Nehru State hospital for mother and child, Shimla. Total 80 patients with asymptomatic high risk singleton pregnancy between 24-28 weeks were included in the study. They were randomly allotted to receive either the progesterone tablet 100 mg intravaginally (Study group) or an identical looking placebo (Control group).Thus both the groups included 40 subjects each. The treatment was continued till 34 weeks of gestation or till PROM/ delivery, whichever was earlier. Method of termination, gestational age at time of delivery, mode and type of delivery, birth weight, apgar score, maternal and perinatal outcome were noted and compared in both groups. All the parameters were statistically analysed by mean + S.D, proportion, frequency, chi-square test. Percentage reduction in the quantitative variables was calculated using the formula of (n-t)/n x100. Results: The incidence of preterm deliveries in the present study was found to be 9.88%. Both the groups were comparable in respect of age, parity, BMI, socioeconomic status, occupation and gestational age at first antenatal visit. There was similarity in both groups in respect to number of previous preterm deliveries and cervical length. The incidence of preterm delivery in the study group was 12.5% and in the control group was 35%. Conclusions: The study concluded that progesterone use was associated with 64.2% reduction in the incidence of preterm delivery (p=0.029).Antenatal administration of progesterone reduces the risk of preterm birth before 37 weeks and 34 weeks as well as the risk of a newborn being born with a birth weight of less than 2500 gms.